Analysis of Learning Methodology Management from the Perspective of Instructional Process Component System Management - Muhamad Faizin; Paisal Aripin; M. Mashuri Nurkulla; Ahmad Subagyo (TA'DIB: Jurnal Pendidikan Agama Islam, 2026)
This study aims to analyze the management of learning methodologies implemented at SMP IT Ash Shiddiqiyyah Tangerang Selatan from the perspective of Instructional Process Component System Management (MSKPI). The study focuses on instructional practices, student engagement, curriculum implementation, and the integration of Islamic educational values in classroom learning. This research employed a qualitative descriptive approach through observation, documentation, and literature review. The findings indicate that instructional activities are still predominantly teacher-centered, with lecture methods more dominant than collaborative and student-centered learning approaches. The implementation of Problem Based Learning, Project Based Learning, and technology integration has not been fully optimized. From the MSKPI perspective, instructional components such as planning, implementation, media utilization, and evaluation have not been systematically integrated. The study concludes that improving instructional quality requires strengthening active learning strategies, enhancing teacher competencies, integrating educational technology effectively, and aligning instructional management with the Merdeka Curriculum and Islamic educational values.